Insights into variability of actinorhodopsin genes of the LG1 cluster in two different freshwater habitats - Jezberová, Jitka; Jezbera, Jan; Hahn, Martin W (PLoS One, 2013)
Actinorhodopsins (ActRs) are recently discovered proteorhodopsins present in Actinobacteria, enabling them to adapt to a wider spectrum of environmental conditions. Frequently, a large fraction of freshwater bacterioplankton belongs to the acI lineage of Actinobacteria and codes the LG1 type of ActRs. In this paper we studied the genotype variability of the LG1 ActRs. We have constructed two clone libraries originating from two environmentally different habitats located in Central Europe; the large alkaline lake Mondsee (Austria) and the small humic reservoir Jiřická (the Czech Republic). The 75 yielded clones were phylogenetically analyzed together with all ActR sequences currently available in public databases. Altogether 156 sequences were analyzed and 13 clusters of ActRs were distinguished. Newly obtained clones are distributed over all three LG1 subgroups--LG1-A, B and C. Eighty percent of the sequences belonged to the acI lineage (LG1-A ActR gene bearers) further divided into LG1-A1 and LG1-A2 subgroups. Interestingly, the two habitats markedly differed in genotype composition with no identical sequence found in both samples of clones. Moreover, Jiřická reservoir contained three so far not reported clusters, one of them LG1-C related, presenting thus completely new, so far undescribed, genotypes of Actinobacteria in freshwaters.
Keywords: bakteriální proteiny; Actinobacteria; DNA, Bacterial; Ecosystem; multigenová rodina; genetická variace; Fresh Water; Sequence Analysis, DNA; Genetic Variation; DNA bakterií; Multigene Family; Molecular Sequence Data; fylogeneze; Austria; Rakousko; polymerázová řetězová reakce; Phylogeny; Czech Republic; ekosystém; sladká voda; sekvenční analýza DNA; hybridizace in situ fluorescenční; Polymerase Chain Reaction; Bacterial Proteins; In Situ Hybridization, Fluorescence; Česká republika; Geography; molekulární sekvence - údaje; zeměpis